Functional Characterization of TNFα in the Starry Flounder (Platichthys stellatus) and Its Potential as an Immunostimulant - Min-Young Sohn; Gyoungsik Kang; Kyung-Ho Kim; Ha-Jeong Son; Chan-Il Park (Animals)
Tumor necrosis factor alpha (TNFα) is a central pro-inflammatory cytokine that mediates host immune responses during infection. In this study, we identified and characterized the TNFα gene in the starry flounder (Platichthys stellatus) through transcriptomic analysis. The deduced protein contained a conserved TNF domain and transmembrane region, and phylogenetic analysis confirmed its homology with other teleost TNFα proteins. Tissue-specific expression profiling revealed high baseline expression in immune-related peripheral organs and a distinct temporal modulation in response to Streptococcus parauberis infection. Recombinant TNFα (rTNFα), produced using a cell-free expression system, significantly enhanced phagocytic activity in peripheral and kidney-derived leukocytes in a dose-dependent manner. Peak activity was observed at 150–200 μg/mL, while a decline at higher concentrations suggested a threshold for immune stimulation. Importantly, hemolysis assays confirmed the safety of rTNFα even at the highest tested concentrations. These results demonstrate the immunomodulatory potential of TNFα as a molecular adjuvant in aquaculture vaccines and underscore its potential utility in immune-enhancing strategies for sustainable aquaculture.